Surgical management and long‐term follow‐up of aberrant right coronary arteries in adults. Issue 6 (30th March 2022) - Bartram, James; Hussain, Azhar; Chaubey, Sanjay; Mittal, Aaina; Khan, Habib; Wendler, Olaf
Abstract: Objectives: Anomalous origins of the right coronary artery (RCA) can cause ischaemia and sudden cardiac death, particularly if the RCA runs between the aorta and pulmonary artery. Conventional coronary artery bypass grafting (CABG) can be affected by early graft failure due to collateral blood flow. We present our institutional experience in managing patients with RCA anomalies. Methods: A single‐center retrospective review of all patients who underwent surgery for aberrant right coronary arteries between 2005 and 2021 was conducted and in‐hospital and long‐term outcomes were analysed at our institution. Results: A total of 10 patients (5 females, median age: 51 years, 36–62) were identified. They presented with symptoms of chest pain ( n  = 8), dyspnoea ( n  = 1) or following cardiac arrest ( n  = 1). In the majority the RCA originated from the left coronary sinus ( n  = 9). In one of those patients and one in whom the RCA originated directly from the left anterior descending artery CABG was performed. The other 8 patients were treated using transfer of the RCA ostium. All patients were discharged home (median hospital stay 5 days, range: 4–10). Four patients experienced post‐op atrial fibrillation. No other complications were observed. At a median follow‐up of 10 years and 9 months, 9 patients were alive and free from cardiac symptoms. One patient died 3 years postsurgery due to liver failure, unrelated to cardiac disease. Conclusions: In patients with an aberrant RCA, transfer of the ostium into the RCS carries a low surgical risk. It overcomes early graft failure in these patients, who present with a dynamic impairment in RCA blood flow. However, if fixed proximal RCA flow‐limiting pathology exists, conventional bypass surgery is feasible.